Kinerja Produksi dan Kinerja Usaha pada Budidaya Ikan Nila (Oreochromis niloticus) di Desa Pulau Terap, Kabupaten Kampar, Riau - Tatag Budiardi; Zumiza Sari; Yani Hadiroseyani; Apriana Vinasyiam (Intek Akuakultur, 2022)
Tilapia (Oreochromis niloticus) is one of the aquaculture commodities that has the potential to be develop as a promising freshwater aquaculture sector in the long term. The condition of the high market and demand for fish consumption has become the goal of the cultivating community in Pulau Terap Village to produce tilapia commodities. However, in cultivation activities, fluctuations in production yields and cycles often occur, it is necessary to study the production process. The purpose of this study was to analyze the production and business performance of tilapia in Pulau Terap Village, Kuok District, Kampar Regency, Riau. This research uses a survey case study method with direct observation, interviews and participating in on-farm cultivation activities to collect data in the field. The results showed that the production of tilapia fish farming in Pulau Terap Village with the KJA system had a better TKH at KJA size 3×6 m by 49.74±2.63%, LPS value was better at KJA size 4×7 m by 3.94 ±0.15%, the RKP value is better for KJA size 4×7 m by 1.16±0.17%, and production is 5,072 tons/unit/year on KJA size 3×6 m. The business performance obtained in this business is PP 0.6 years and R/C 1.5 so that the business is feasible to continue and in future production development it is more recommended to use KJA measuring 3 × 6 m.